2014
DOI: 10.1080/01626620.2014.977702
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Motivation Theory and Supplemental Workshops on First-Time Passing Rates of HBCU Teacher Candidates

Abstract: The action research methodology for this study reports descriptive statistical findings from the performance of 19 Early Childhood Education African American teacher candidates matriculating through a state-approved program at an HBCU. Researcher-moderators provided a treatment plan of focused summer workshops, conceptualized based upon the findings of low first-time passing rates on the Early Childhood Education Exam, predominately content knowledge in social studies and reading. The action researchers sugges… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
0
0
1

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 18 publications
1
0
0
1
Order By: Relevance
“…Discussion and Conclusions: Findings revealed that while the attitudes of participating prospective teachers towards teaching profession is increasing, their academic motivations and general academic grade-point averages are also increasing too. It can be assumed that true love to their professions and high motivation might be the factors affecting the success of prospective teachers' performances (Moffett, Frizzell, Brownlee-Williams & Thompson, 2014). It is worth noting that the attitudes towards teaching as a profession, academic motivation and achievement are all intertwined factors yielding similar impacts based on our findings.…”
Section: Purpose and Significancesupporting
confidence: 68%
See 1 more Smart Citation
“…Discussion and Conclusions: Findings revealed that while the attitudes of participating prospective teachers towards teaching profession is increasing, their academic motivations and general academic grade-point averages are also increasing too. It can be assumed that true love to their professions and high motivation might be the factors affecting the success of prospective teachers' performances (Moffett, Frizzell, Brownlee-Williams & Thompson, 2014). It is worth noting that the attitudes towards teaching as a profession, academic motivation and achievement are all intertwined factors yielding similar impacts based on our findings.…”
Section: Purpose and Significancesupporting
confidence: 68%
“…Hui, Sun, Sau-Yan Chow ve Ho-Tat Chu, (2011) yaptıkları araştırmada akademik motivasyonu etkileyen değişkenleri incelemiş ve sırasıyla kendini yeterli hissetme, bir gruba ait olma ve anne-babaya duyulan saygının akademik motivasyon üzerinde etkili olduğunu belirtmiştir. Maslow'un motivasyon teorisine göre de karşılanmamış olan ihtiyaçları insanları motive etmektedir ve daha yüksek ihtiyaçlar için de öncelikle belirli alt ihtiyaçların karşılanması gereklidir (Moffett, Frizzell, Brownlee-Williams & Thompson, 2014). Bireyin sahip olduğu becerileri ve gerçekçi gelecek planları gibi kişisel özelliklerin içsel motivasyonu daha çok etkileyen bir unsur olduğu düşünüldüğünde (Jugović, Marušić, Ivanec & Vidović, 2012) bu durumun akademik motivasyon üzerinde de etkili olabileceği düşünülmektedir.…”
Section: Sonuç Ve Tartışmaunclassified